Flood risk assessment and channel roughness adjustment modeling in a degraded Baliase River basin, Indonesia - Yumna, Yumna; Sapareng , Sukriming; Nur , Burhanuddin; Soma, Andang Suryana; Akmal , Akmal (Journal of Degraded and Mining Lands Management, 2025)
Land degradation in the Baliase River Basin continues to worsen due to increasingly complex hydrological phenomena. This study aimed to evaluate peak discharge as a flood reference for a return period of 2–200 years, estimate channel capacity, determine flood risk status, and simulate hydraulic responses to variations in Manning's n value. Peak discharge calculations use the Nakayasu synthetic unit hydrograph method, with field geometric data modeled using HEC-RAS 6.0 software in a steady-state manner. Four technical scenarios were tested: (1) river normalization, (2) clearing of wild vegetation, (3) bank hardening, and (4) channel deepening/straightening. The analysis results indicate that the Baliase River Basin is generally in critical flood conditions, especially in the downstream and central areas (Stations 6-14). Most river segments are unable to accommodate peak discharges for a repeat period of 2 years. The variation in the n value in each scenario suggests that technical intervention can significantly alter the hydraulic characteristics. Adjusting n values can reduce flood risk, primarily through changes in hydraulic form. Scenario 4 is most effective because it increases the cross-sectional area and hydraulic radius, while Scenarios 1 and 3 contribute by reducing channel roughness. Scenario 2 serves as a support strategy and is ideally combined with other strategies. Priority is given to Scenario 4 in areas where discharge exceeds channel capacity.